2020
DOI: 10.22271/chemi.2020.v8.i3j.9299
|View full text |Cite
|
Sign up to set email alerts
|

Influence of plant spacing, nutrient levels and foliar nutrition on growth, yield and quality of dual purpose sorghum K12 under rainfed condition

Abstract: Field experiment was conducted at Agricultural Research Station, Kovilpatti during rabi season (October 2017 to January 2018) to find out the suitable plant geometry, levels of fertilizers and foliar spray of micronutrients (Zn and Fe) at 15, 30 and 45 DAS to improve the growth and yield of sorghum variety K12 (dual purpose). The experiment was laid out in randomized block design with three replication and twelve treatments. The treatment consists of two plant geometry, three different dose of fertilizer and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
1
1
0
Order By: Relevance
“…Aasif et al [15] and Kafle et al [23] also reported higher crop yield in poultry manure treatments. Similar results were also observed by Almaz et al [24], Surve et al [17] and Bharathi et al [21].…”
Section: Effect Of Different Nitrogen Sources On Yield and Harvest In...supporting
confidence: 91%
See 1 more Smart Citation
“…Aasif et al [15] and Kafle et al [23] also reported higher crop yield in poultry manure treatments. Similar results were also observed by Almaz et al [24], Surve et al [17] and Bharathi et al [21].…”
Section: Effect Of Different Nitrogen Sources On Yield and Harvest In...supporting
confidence: 91%
“…number of tillers (m 2 ) and test weight (g) as well as higher nutrient uptake by the crop. This might be due to that the grain yield depends on the synthesis and accumulation of photosynthates and their distribution among various plant parts as well as the extent of translocation into sink (grains) and also on plant growth and development during early stages of crop growth which in turn depends on the availability of nutrients, [20,21]. The yield in the treatment T 2 was statistically at par with T 3 , T 7 and T 11 because of the combined application of manures and chemical fertilizer, there was an increase in availability of nutrients which provide higher amount of nutrients to the crop [22].…”
Section: Effect Of Different Nitrogen Sources On Yield and Harvest In...mentioning
confidence: 99%